MODEL PROBLEM BASED LEARNING DAN PRESPEKTIF GENDER TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA - Bedilius Gunur; Apolonia Hendrice Ramda (Jurnal Numeracy, 2020)
This research aims to; 1) comparing the Problem Based Learning model with the direct learning model from the perspective of students' mathematical reasoning abilities. 2). Look at the interaction of effects between learning models and gender on students' mathematical reasoning abilities. The design of this study used a 2 x 2 factorial design. Sampling was carried out using a simple random sampling technique by first conducting a class equality test. Data was collected using a test technique in the form of a question matter. Data were analyzed using two-way ANOVA. The analysis shows that; 1). The problem-based learning model of learning is better than the direct learning model in terms of students 'mathematical punishment abilities, 2. There was no interaction between the learning models used with the gender on the students' mathematical punishment abilities of students. Both male and female students requested compilation to be taught by applying the problem-based learning model to the direct learning model. Abstrak Penelitian ini bertujuan untuk; 1) membandingkan model Problem Based Learning dengan model pembelajaran langsung dalam perspektif kemampuan penalaran matematis siswa. 2). Melihat interaksi efek antara model pembelajaran dan gender terhadap kemampuan penalaran matematis siswa. Rancangan penelitian ini menggunakan desain factorial 2 x 2. Pengambilan sampel dilakukan dengan menggunakan teknik simpel random sampling dengan terlebih dahulu melakukan uji kesetaraan kelas. Data dikumpulkan dengan menggunakan teknik tes dengan bentuk soal uraian. Data dianalisis menggunakan ANAVA dua jalur. Hasil analisis menunjukan bahwa; 1). Model pembelajaran problem based learning lebih baik dibandingkan model pembelajaran lansung dalam hal kemampuan penalaran matematis siswa, 2. Tidak terdapat efek interaksi antara model pembelajaran yang digunakan dengan gender terhadap kemampuan penalaran matematis siswa. Baik siswa laki-laki maupun siswa perempuan sama baiknya ketika dibelajarkan dengan menerapkan model pembelajaran problem based learning dari pada model pembelajaran lansung. Kata Kunci: Problem Based Learning; Gender; Penalaran Matematis